From cradle to grave: How to loot a 401(k) plan - Stanton, Richard (Journal of Financial Economics, 2000)
The regulations governing asset distributions from many retirement plans give participants the option to time retirement or rollovers from the plan strategically. They possess a long-lived put option, whose exercise price resets periodically to the current value of the assets in the plan. I derive a recursive closed-form valuation formula for the option and develop a numerical algorithm for implementing the result. I find that, for reasonable assumptions about volatility and life expectancy, the option's value may approach 40% of the value of the assets in the plan, financed entirely by those still contributing. This wealth transfer can, however, be easily avoided by making a simple change to the current regulations governing valuation and payout of these retirement plans.